Intrusion-Detection System Based on Fast Learning Network in Cloud Computing - Mohammed Hasan, Ali; Mohamad Fadli, Zolkipli (American Scientific Publisher, 2018)
Detection of attacks in the computers and networks keeps being the pertinent and challenging area of researchers. Intrusion-Detection System is an essential technology of Network Security. Currently, Intrusion Detection still faces some challenges like huge amounts of data to process, high averages of false alarms and low detection rates., especially in cloud environment which more vulnerable to attacks. This paper includes an overview of the intrusion-detection system and introduces to the reader some fundamental concepts of IDS work in cloud computing, also propose a new algorithm Fast Learning Network to work based on an intrusion detection.